Competence, knowledge, and the labour market: the role of complementarities - Donatella Gatti (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper develops a theoretical analysis of training regimes as outcomes of a complementarity between organizational and institutional factors that determine firms' and workers' incentives as regards skills. Specifically, the paper proposes that, on the one hand, knowledge embeddedness within firms is the determinant of firms' preferences concerning training, while, on the other, labor market institutionalization provides the framework for workers' preferences. Applying a criterion of coherence between firm and worker incentives, two stable configurations are singled out. The former is shown to correspond to the Japanese model of training, while the latter conforms more to the German experience. – – In dieser Studie wird eine theoretische Analyse der institutionellen Regelungen zur beruflichen Bildung vorgestellt. Sie werden als Ergebnis einer gegebenen Komplementarität organisatorischer und institutioneller Faktoren verstanden, die für Unternehmen und Arbeitnehmer als Anreize für Aktivitäten wirken, die sich auf berufliche Fähigkeiten beziehen. Die Analyse legt nahe, daß für Unternehmen die Anpassung der Wissensbestände an ihre spezifischen Anforderungen besonders wichtig ist, während es für die Arbeitnehmer die institutionellen Regelungen auf dem Arbeitsmarkt sind. Wird ein Parameter eingeführt, der das Maß der (Nicht-)Übereinstim-mung zwischen den Anreizen für die Unternehmen und für die Arbeitnehmer abbildet, dann lassen sich zwei stabile Konstellationen herausfinden. Eine entspricht mehr dem japanischen Modell der beruflichen Ausbildung, das andere mehr den deutschen Erfahrungen.
Keywords: D21; I20; J51; P51; 330; institutional complementarity; incentives; training; labor market institutions; company organization.; Berufsbildung; Weiterbildung; Ökonomischer Anreiz; Wissen; Tarifpolitik; Institutionalismus; Theorie; Welt